Faktor-Faktor yang Memengaruhi Remaja di Indonesia Menjadi Kecanduan terhadap Minuman Beralkohol - Ida Bagus Agung Permana Manuaba; David Hizkia Tobing (Lembaga Pengembangan Kinerja Dosen, 2025)
Alcohol abuse is a growing problem around the world. Especially in adolescents, alcoholic beverages are often consumed excessively for specific purposes. Looking at the problem, the question arises what influences adolescents to become addicted to alcohol, so this paper aims to find out what factors influence adolescents in Indonesia to become addicted to alcohol. This research was conducted using a descriptive literature review method. Literature was searched and found through Google Scholar with the keywords